2014
DOI: 10.1007/s13277-014-2971-0
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutation analysis in chronic lymphocytic leukemia: comparison of different detection methods

Abstract: TP53 gene defects represent a strong adverse prognostic factor for patient survival and treatment resistance in chronic lymphocytic leukemia (CLL). Although various methods for TP53 mutation analysis have been reported, none of them allow the identification of all occurring sequence variants, and the most suitable methodology is still being discussed. The aim of this study was to determine the limitations of commonly used methods for TP53 mutation examination in CLL and propose an optimal approach for their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Numerous commercially available ready-to-use analytical kits include the TP53 gene, and ERIC is conducting a multi-center collaborative effort to assess and compare various pre-designed and custom gene panel technologies. Previous studies exploring the inter-reproducibility of targeted NGS and Sanger sequencing for TP53 analysis demonstrated very good correlation of the results, specifically showing that all variants detected by Sanger sequencing are also detectable by NGS [ 22 , 23 , 32 35 ]. A recent study also showed an excellent correlation between the results obtained from two different NGS platforms, namely, the Ion PGM (ThermoFisher) and the MiSeq (Illumina) [ 33 ].…”
Section: Procedures Descriptionmentioning
confidence: 97%
“…Numerous commercially available ready-to-use analytical kits include the TP53 gene, and ERIC is conducting a multi-center collaborative effort to assess and compare various pre-designed and custom gene panel technologies. Previous studies exploring the inter-reproducibility of targeted NGS and Sanger sequencing for TP53 analysis demonstrated very good correlation of the results, specifically showing that all variants detected by Sanger sequencing are also detectable by NGS [ 22 , 23 , 32 35 ]. A recent study also showed an excellent correlation between the results obtained from two different NGS platforms, namely, the Ion PGM (ThermoFisher) and the MiSeq (Illumina) [ 33 ].…”
Section: Procedures Descriptionmentioning
confidence: 97%
“…Techniques frequently used for assessing TP53 status in CLL include FISH for del(17p), Sanger sequencing, and next-generation sequencing for TP53 mutations ( Table 2 ). 27 , 35 , 74 , 75 As TP53 mutations are associated with a poor prognosis independently of the presence of del(17p), 7 it is important to assess for TP53 mutation status using a sequencing technique. 27 , 35 …”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing technologies include targeted next-generation sequencing, which has good correlation with Sanger sequencing in comparison studies 12 , 28 , 31 , 35 , 75 , 78 and detects low-frequency mutations below the threshold for Sanger sequencing. 38 , 79 81 The sensitivity threshold varies depending on a number of variables, including the hardware, methods used for testing and the analytical pipeline, and should be defined by each laboratory using standardized criteria or equivalent medical laboratory standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of mutations identified by this method was the same as that of the DHPLC analysis followed by the Sanger sequencing. 48 …”
Section: Introductionmentioning
confidence: 99%